Caracterização de formações superficiais oxídicas na superfície geomórfica de Trindade do Sul – Alto Uruguai/RS - Soares, Denise Hobold (2024)
The aim of this study was to characterize the oxidic formations representing the geomorphic surface of Trindade do Sul/RS, located on the Araucarias Plateau and developed on a volcanic substrate of the Serra Geral Group, a humid subtropical environment. To achieve this goal, field and laboratory work was necessary. The field work was carried out with the aim of individualizing the materials in macromorphological terms and collecting samples for analysis. In the laboratory, different procedures were carried out with the collected material, including: macromorphological description of the materials that make up the section and the clasts that make up the Stone Line; granulometric determination; macronutrient chemistry; sulfuric attack of the clay fraction; iron content (free, total and amorphous); total quantitative chemical analysis by X-ray fluorescence spectrometry (XRF); mineralogy by X-ray diffraction (XRD) and micromorphology. The section studied corresponds to a vertical cut exposed on the RS 324 highway. It is located at an altitude of 633 meters and corresponds to the fourth level of dissected plateaus on the left bank of the Alto Uruguai river, the lower course of the Passo Fundo river. The macromorphological description of the materials at the top of the dissected plateau revealed deep surface formations (900cm), the volumes of which correspond to the sequence of horizons: Ap, AB, Bw1, Bw2 and BC, with the presence of a line of stones at 720cm. The macromorphological attributes, macronutrients and the results of the sulphuric attack indicate that this is a very clayey Latosol Bruno Distróférrico, with a very hard consistency when dry and friable when wet. At the transition from Bw2 to BC there is a line of stones made up of rounded fragments, black in color with yellowish spots, with a smooth to slightly rough texture. X-ray fluorescence (XRF) of the clasts indicated a concentration of Fe2O3 (77.4%), followed by Al2O3 (5.5%) and SiO2 (2.8%). This high percentage of iron suggests that these fragments originated before the pedogenized material, proving the allochthonous nature of the overlying materials. The iron content (free, total and amorphous) indicates surface cover with an advanced stage of weathering, which can be interpreted as older materials in the surface volumes and younger materials in the volumes at the base of the section. Mineralogical analysis of the clay fraction revealed minerals from the phyllosilicate family (kaolinite, interlayered hydroxy vermiculite) and the oxide and hydroxide class (gibbsite, goethite and hematite, anatase, rutile). Kaolinite and gibbsite indicate conditions of monosialitization-type pedogeochemical formations. The micromorphological description is marked by the presence of pedorelike, lithorelike, and recurrent iron oxide migration in the materials above the Stone Line. Thus, the materials corresponding to the initial 720 cm of the representative section of Trindade do Sul/RS indicate an allochthonous nature. This confirms, in the sector of the Araucaria Plateau analyzed, the role of Etchplanationrelated relief sculpting processes, as already verified in other sectors of this plateau.